PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN POWERPOINT MORPH UNTUK SISWA KELAS II SD NEGERI 2 SAWA - Yunus, Ardiansyah; Razilu, Zila; Fajriani, Alfiah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to develop interactive learning media using PowerPoint Morph for second-grade students at SD N 2 Sawa, with a focus on Indonesian language subjects. In today's digital era, the use of technology in education is very important to improve learning effectiveness and create an attractive and interactive learning environment for students. The method used in this study follows the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The results of the analysis show that second-year students have difficulty understanding Indonesian language lesson material when using conventional learning media. Therefore, PowerPoint Morph was designed with an attractive and interactive display, using hardware such as laptops and mobile phones to increase student motivation to learn. Media testing shows that the developed PowerPoint obtained an excellent validation score from media experts, with a percentage of 89.72% after revision, and student test scores reached 91.40% for individuals and 95.20% for small groups. The conclusion of this study is that the development of interactive learning media using PowerPoint Morph is feasible to be applied in the learning process because it can increase students' interest and motivation to learn. Thus, PowerPoint Morph can be an effective alternative in supporting learning in elementary schools, especially in Indonesian language lessons. ABSTRAKPenelitian Ini Bertujuan Untuk Mengembangkan Media Pembelajaran Interaktif Menggunakan Powerpoint Morph Untuk Siswa Kelas II Di SD N 2 Sawa, Dengan Fokus Pada Mata Pelajaran Bahasa Indonesia. Dalam Era Digital Saat Ini, Pemanfaatan Teknologi Dalam Pendidikan Menjadi Sangat Penting Untuk Meningkatkan Efektivitas Pembelajaran Dan Menciptakan Suasana Belajar Yang Menarik Dan Interaktif Bagi Siswa. Metode Yang Digunakan Dalam Penelitian Ini Mengikuti Model Pengembangan ADDIE, Yang Mencakup Analisis, Desain, Pengembangan, Penerapan, Dan Evaluasi. Hasil Analisis Menunjukkan Bahwa Siswa Kelas II Mengalami Kesulitan Dalam Memahami Materi Pelajaran Bahasa Indonesia Ketika Menggunakan Media Pembelajaran Konvensional. Oleh Karena Itu, Powerpoint Morph Dirancang Dengan Tampilan Yang Menarik Dan Interaktif, Menggunakan Perangkat Keras Seperti Laptop Dan Handphone Untuk Meningkatkan Motivasi Belajar Siswa. Uji Coba Media Menunjukkan Bahwa Powerpoint Yang Dikembangkan Memperoleh Skor Validasi Yang Sangat Baik Dari Ahli Media, Dengan Persentase 89,72% Setelah Revisi, Dan Skor Uji Coba Siswa Mencapai 91,40% Untuk Individu Dan 95,20% Untuk Kelompok Kecil. Kesimpulan Dari Penelitian Ini Adalah Bahwa Pengembangan Media Pembelajaran Interaktif Menggunakan Powerpoint Morph Layak Diterapkan Dalam Proses Pembelajaran, Karena Dapat Meningkatkan Minat Dan Motivasi Belajar Siswa. Dengan Demikian, Powerpoint Morph Dapat Menjadi Alternatif Yang Efektif Dalam Mendukung Pembelajaran Di Sekolah Dasar, Khususnya Dalam Pelajaran Bahasa Indonesia